Theistic modal realism and causal modal collapse - Maia, Nuno ca. 20./21. Jh. (Religious studies, 2021)
Theistic modal realism argues for an extension of Lewis's modal realism capable of accommodating a theistic God. By affording elegant solutions to many atheistic challenges, the view is of great theoretical utility for the theist. However, it has been objected that within a Lewisian framework God cannot be causally efficacious on pain of collapsing intuitively distinct modal notions. In this article I explain why these worries are ill-founded and show how God's existence and causal power over the pluriverse can be consistently understood. If successful, the proposal offers a congenial theistic way to adopt modal realism and address the atheological problems.